1985
DOI: 10.2170/jjphysiol.35.1023
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic responses and adaptations to swimming training and hypobaric hypoxia in postnatal rats.

Abstract: Twenty four male Sprague-Dawley rats, 35 days old, were randomly assigned to one of four groups : 2 resting control groups and 2 swimming groups. The sea level-control and the sea level-swimming groups were housed 5 weeks at 1,011 hPa (760 mmHg) while the hypoxic control and swimming groups were housed for 1 week at 678 hPa, followed by 4 weeks at 611 hPa. The swimming rats were subjected to a swimming program of 30 min, 6 days/week for 5 weeks. Both hypoxia groups developed significantly higher Hb and Hct lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1990
1990
2005
2005

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…Vats et al, 1999, found increased liver glycogen by day 1 of exposure and subsequently, decreased liver glycogen towards the end of a 21-day exposure period along with decreased glycogen synthetase activity. The altitude-induced decrease in muscle glycogen is consistent with results of previous studies (Blume & Pace, 1967;Taguchi et al, 1985;Bigard et al, 1996). Bigard et al (1996) demonstrated that glycogen stores in the muscle, particularly soleus, were altered by both decreased energy intake and hypoxia per se.…”
Section: Discussionsupporting
confidence: 90%
“…Vats et al, 1999, found increased liver glycogen by day 1 of exposure and subsequently, decreased liver glycogen towards the end of a 21-day exposure period along with decreased glycogen synthetase activity. The altitude-induced decrease in muscle glycogen is consistent with results of previous studies (Blume & Pace, 1967;Taguchi et al, 1985;Bigard et al, 1996). Bigard et al (1996) demonstrated that glycogen stores in the muscle, particularly soleus, were altered by both decreased energy intake and hypoxia per se.…”
Section: Discussionsupporting
confidence: 90%
“…This result raises the possibility that fiber type transformation occurs, at least partially, via a cellular oxygen-sensing mechanism. After chronic exposure to a hypoxic atmosphere, some studies did not observe any significant differences in fiber composition of the SOL [24][25][26], whereas others reported fiber type transformation of slow-twitch (SO) fibers into fast-oxidative-glycolytic (FOG) fibers in the same muscle [27].…”
Section: Discussionmentioning
confidence: 99%
“…Muscle samples frozen for histochemical analyses were sectioned (10 μm thick) in a cryostat at −20°C. The sections were stained for myosin adenosine triphosphatase (ATPase), succinate dehydrogenase (SDH), and α‐glycerophosphate dehydrogenase (α‐GPD) according to previous studies (Wattenberg & Leong, 1960; Taguchi et al 1985).…”
Section: Methodsmentioning
confidence: 99%